2018
DOI: 10.3390/molecules23081857
|View full text |Cite
|
Sign up to set email alerts
|

Oregano Essential Oil Attenuates RAW264.7 Cells from Lipopolysaccharide-Induced Inflammatory Response through Regulating NADPH Oxidase Activation-Driven Oxidative Stress

Abstract: Oregano is an aromatic plant widely distributed throughout the Mediterranean area and in Asia. Recent studies have revealed that the anti-inflammatory effect of essential oil in this plant. However, the mechanisms underlying the therapeutic potential have not been well elucidated. This study determined whether oregano essential oil (OEO) exerts an anti-inflammatory effect on lipopolysaccharide (LPS)-treated murine macrophage cells (RAW264.7 cells) in vitro and elucidated the possible underlying molecular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 38 publications
(49 reference statements)
1
35
1
Order By: Relevance
“…Oregano EO protects against the LPS-induced cell inflammatory response through the NADPH oxidase/ROS pathway. [362] Similarly, the results of the anti-inflammatory tests on sage essential oils using murine macrophages indicate that these oils significantly (p < 0.05) reduced nitric oxide (NO), and NF-κB production in murine macrophage cells. [363] The antiinflammatory activity of rosemary EO is mainly attributed to its main compounds 1,8-cineole, αpinene, and camphor.…”
Section: Eos and Human Healthmentioning
confidence: 97%
See 1 more Smart Citation
“…Oregano EO protects against the LPS-induced cell inflammatory response through the NADPH oxidase/ROS pathway. [362] Similarly, the results of the anti-inflammatory tests on sage essential oils using murine macrophages indicate that these oils significantly (p < 0.05) reduced nitric oxide (NO), and NF-κB production in murine macrophage cells. [363] The antiinflammatory activity of rosemary EO is mainly attributed to its main compounds 1,8-cineole, αpinene, and camphor.…”
Section: Eos and Human Healthmentioning
confidence: 97%
“…Specifically, for our five essential oils, the anti‐inflammatory activity has been recently reported for oregano essential oil on lipopolysaccharide (LPS)‐treated murine macrophage cells. Oregano EO protects against the LPS‐induced cell inflammatory response through the NADPH oxidase/ROS pathway . Similarly, the results of the anti‐inflammatory tests on sage essential oils using murine macrophages indicate that these oils significantly ( p <0.05) reduced nitric oxide (NO), and NF‐ κ B production in murine macrophage cells .…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 99%
“…Previous studies demonstrated levels of IL-6, IL-8, and TNF-α were significantly elevated in participants with obesity [32,33]. Cheng et al [34] found that secretion of IL-1β, IL-6, and TNF-α was increased in LPS-treated murine macrophage cells in vitro through the activation of NF-κB pathway. Circulating levels of IL-6 were significantly higher in diet-induced obese mice than in Lean mice.…”
Section: Discussionmentioning
confidence: 97%
“…In this cellular system, the oregano essential oil was able to inhibit the expression and secretion of IL-1β, IL-6 and TNF-α and to reduce the activation of MAPK, IκB and NF-κB. Moreover, oregano essential oil also inhibited the LPS-induced RAW264.7 cell inflammation through the NADPH oxidase-mediated production of reactive oxygen species (ROS) [18].…”
mentioning
confidence: 95%
“…In LPS-stimulated RAW 264.7 cells, the butenolide derivative n-butyl bracteanolide A showed higher NO inhibitory production than bracteanolide A isolated from the plant [17]. Essential oils have been described as possessing in vitro and in vivo anti-inflammatory activities [18]. The authors studied the effect of the essential oil of oregano-mainly constituted by carvacrol-on the NADPH oxidase mediated oxidative stress and the anti-inflammatory activity using LPS-induced RAW264.7 macrophages.…”
mentioning
confidence: 99%